Early stage detection and classification of colon cancer using deep learning and explainable AI on histopathological images - Hossain, Mainul; Haque, Shataddru Shyan; Ahmed, Humayun; Mahdi, Hossain Al; Aich, Ankan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.